Erwachsenenbildung und Lernen in Zeiten von Globalisierung, Transformation und Entgrenzung - Dörner, Olaf (Schriftenreihe der Sektion Erwachsenenbildung in der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2020)
Against the background of analyzes on transformation, reflexive modernization and fleeting modernity, adult education is required to confront social processes of change, the dissolution of boundaries and structural upheavals. Adult education and learning are part of these changes, each specific, but also contributing to change. The volume gathers selected and reviewed conference papers by the scientists who presented their work at the annual conference.